Activation of Myd88-Dependent TLRs Mediates Local and Systemic Inflammation in a Mouse Model of Primary Sjögren's Syndrome - Kiripolsky, Jeremy; Romano, Rose-Anne; Kasperek, Eileen M.; Yu, Guan; Kramer, Jill M. (Frontiers in Immunology, 2020)
Toll-like receptors (TLRs) are important mediators of chronic inflammation in numerous autoimmune diseases, although the role of these receptors in primary Sjögren’s syndrome (pSS) remains incompletely understood. Previous studies in our laboratory established Myd88 as a crucial mediator of pSS, although the disease-relevant ligands and the upstream signaling events that culminate in Myd88 activation have yet to be established. The objective of this study was to identify specific Myd88-dependent TLR-related pathways that are dysregulated both locally and systemically in a mouse model of pSS (NOD.B10Sn-H2b/J (NOD.B10)). We performed RNA-sequencing on spleens derived from NOD.B10 mice. We then harvested salivary tissue and spleens from Myd88-sufficient and deficient C57BL/10 (BL/10) and NOD.B10 mice and performed flow cytometry to determine expression of Myd88-dependent TLRs. We cultured splenocytes with TLR2 and TLR4 agonists and measured production of inflammatory mediators by ELISA. Next, we evaluated spontaneous and TLR4-mediated inflammatory cytokine secretion in NOD.B10 salivary tissue. Finally, we assessed spontaneous Myd88-dependent cytokine secretion by NOD.B10 salivary cells. We identified dysregulation of numerous TLR-related networks in pSS splenocytes, particularly those employed by TLR2 and TLR4. We found upregulation of TLRs in both the splenic and salivary tissue from pSS mice. In NOD.B10 splenic tissue, robust expression of B cell TLR1, TLR2, and TLR6 required Myd88. Splenocytes from NOD.B10 mice were hyper-responsive to TLR2 ligation and the endogenous molecule decorin modulated inflammation via TLR4. Finally, we observed spontaneous secretion of numerous inflammatory cytokines and this was enhanced following TLR4 ligation in female NOD.B10 salivary tissue as compared to males. The spontaneous production of salivary IL-6, MCP-1 and TNF alpha required Myd88 in pSS salivary tissue. Thus, our data demonstrate that Myd88-dependent TLR pathways contribute to the inflammatory landscape in pSS, and inhibition of such will likely have therapeutic utility.